2010
DOI: 10.1002/ab.20373
|View full text |Cite
|
Sign up to set email alerts
|

The neurocognition of conduct disorder behaviors: specificity to physical aggression and theft after controlling for ADHD symptoms

Abstract: There is growing evidence that among the different conduct disorder (CD) behaviors, physical aggression, but not theft, links to low neurocognitive abilities. Specifically, physical aggression has consistently been found to be negatively related to neurocognitive abilities, whereas theft has been shown to be either positively or not related to neurocognition. The specificity of these links needs further examination because attention deficit hyperactivity disorder (ADHD) links to both physical aggression and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 72 publications
1
29
1
2
Order By: Relevance
“…The subcategory of aggression to people and animals as well as the subcategory of deceitfulness and theft are associated with ODD behaviors. Moreover, in contrast with the findings of other reports, person-oriented or property-oriented conduct behaviors are not associated with the ODD score or ADHD severity [18,19]. The current results show that the hyperactivity/impulsivity score is associated with the destruction of property subcategory, whereas the inattentiveness score is associated with the aggression to people or animals subcategory.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The subcategory of aggression to people and animals as well as the subcategory of deceitfulness and theft are associated with ODD behaviors. Moreover, in contrast with the findings of other reports, person-oriented or property-oriented conduct behaviors are not associated with the ODD score or ADHD severity [18,19]. The current results show that the hyperactivity/impulsivity score is associated with the destruction of property subcategory, whereas the inattentiveness score is associated with the aggression to people or animals subcategory.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, CD in girls with ADHD is a risk factor for academic, psychiatric, and sexual behavior problems [17]. In addition, CD in inmates of juvenile detention centers is associated with a lower educational and occupational level of the father [18].…”
Section: Association Of Conduct Disorder and Oppositional Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Walsh (1987) reports the familiar relationship between low verbal ability and violence in his study of male probationers. In contrast, probationers with the highest verbal abilities engaged in more serious property offending (also see Barker et al, 2011). …”
mentioning
confidence: 99%
“…This distinction may also be referred to the contrast between offenses against persons and property offenses, or to the contrast between overt and covert delinquency. A number of studies have shown that poor cognitive function was reliably reported for aggressive antisocial behavior, particularly for physical aggression, and that non-aggressive problems were either not associated or positively associated with cognitive function in both males and females (Barker et al, 2007(Barker et al, , 2011Giancola & Mezzich, 2000;Giancola, Mezzich, & Tarter, 1998;Hancock, Tapscott, & Hoaken, 2010;Larivée et al, 1994;Walsh, 1987), though the latter have been less studied.…”
Section: Antisocialmentioning
confidence: 99%